1970
DOI: 10.3329/bmj.v40i1.9963
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Posterior Fossa Tumor Surgery Without Preoperative Ventriculo-peritoneal Shunt

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Although the incidence of CSF leakage after posterior fossa surgery has been quoted to be as high as 26.7%14, the incidence ranges between 4 and 17% in most series 10,15. The incidence of 17% in our study was thus similar to these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Although the incidence of CSF leakage after posterior fossa surgery has been quoted to be as high as 26.7%14, the incidence ranges between 4 and 17% in most series 10,15. The incidence of 17% in our study was thus similar to these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Another investigation found just one occurrence of fatality, at 0.83 percent. 12 According to the most recent study, the mortality rate was 6.7 percent. 8…”
Section: Discussionmentioning
confidence: 98%
“…CSF leakage and pseudomeningocele were similarly shown to be the most prevalent postoperative complications in our study, accounting for about 15% of patients. Islam et al 12 reported that CSF leak was the commonest complication (26%), followed by pseudomeningocele (23%). Shaikh et al 13 researched 66 patients and found that medulloblastoma (29.26 percent) and pilocytic astrocytoma (29.26 percent) were the most prevalent posterior fossa brain tumors, which is very same as our study, which included 13 (32.5 percent) medulloblastoma and astrocytoma (32.5 percent).…”
Section: Discussionmentioning
confidence: 99%
“…Relieving the hydrocephalus in the presence of posterior fossa tumor can cause sudden decompression. It may lead to the formation of extradural hematoma [18]. ETV and VP shunt are recommended as permanent treatment for hydrocephalus after posterior fossa tumor surgery [11].…”
Section: Discussionmentioning
confidence: 99%